A Sociolinguistic Study on Language Contact between Algerian Deaf and Hearing Communities on Social Media - CHERIF, ZOHRA MERIEM (My University, 2020)
The purpose of this investigation is to examine the sociolinguistic phenomenon of language contact between Algerian Hearing and Deaf communities on social media. The study is motivated by three problematics: “Is communication between Deaf and Hearing Algerians on social media possible? If yes, what are the features/strategies of such linguistic contact?”, “Do speakers from both communities influence each other’s use of language while communicating?”, and “Are interpreters aware of such communication?” To answer these questions, this investigation attempts to replicate the study of C. Lucas and C. Valli on Language contact between ASL and English. Two research methods were used: an interview with Sign language interpreters from different regions and a covert observation of Deaf Algerian people of varied ages on different social networks. Findingsshowed that this particular linguistic contact is possible on various platforms of social media and that it generates some distinctive features different from the outcomes of the original study.
Keywords: Sociolinguistics; Language contact; Deaf and Hearing communities; Social media; Linguistic outcomes